PEMANFAATAN ASAP CAIR KAYU PINUS (Pinus merkusii Jungh. & de Vriese) SEBAGAI KOAGULAN GETAH KARET - Santiyo Wibowo; Gustan Pari; Raden Esa Pangersa Gusti (Pusat Penelitian dan Pengembangan Hasil Hutan, 2016)
Smoke liquid is a liquid obtained from smoke condensation during charcoal firing process. The main content of the smoke liquid is acetic acid, hence, can be used as an alternative latex coagulant. Acid in vinegar can reduce the pH of latex and cause the latex to coagulate rapidly. This paper determines effectiveness of using smoke liquid as a latex coagulant and characteristics of the treated latex. The smoke liquid in this study was derived from pine wood. The smoke liquid solutions consisted of the crude smoke liquid and the diluted solution in various concentrations of 5, 10, 15 and 20%. The smoke liquid solution was then each poured into a container of latex. Testing was undergone by observing latex coagulating time, coagulate condition, texture, color, odor and homogenity. The most effective smoke liquid which produced the best latex based on its performances was then taken for further testing of physico-chemical properties which included dry rubber content, plasticity retention index (PRI), initial plasticity (Po), final plasticity (Pa), dirt content, ash content, volatile matter content (Vm), and nitrogen content. Results were then compared with the conventional use of formic acid as a control coagulant. The result showed that the crude and distillate smoke liquid solutions with concentration of 10% produced the best coagulantperformances than the other solutions. Rubber latex treated with the crude smoke liquid produced the best physico-chemical properties and could meet requirements of the Indonesian National Standard (SNI) for Rubber Quality.